Implementation of the Learning Through Play Method in Developing the Cognitive Abilities of Group B Children at TK Bakti Angkasa Semuli Jaya - M, Martoyo; Marfuah, Siti (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to describe in depth the implementation of the play-based learning method in developing the cognitive abilities of Group B children at TK Bakti Angkasa Semuli Jaya. This research uses a qualitative approach with a descriptive design. The subjects of the study consisted of the classroom teacher and Group B children. Data collection techniques were carried out through participatory observation, in-depth interviews, and documentation. Data analysis was conducted using data reduction, data display, and conclusion drawing. The results of the study indicate that the play-based learning method is implemented through various activities such as educational games, group activities, and the use of concrete learning media. This method is able to create a joyful learning atmosphere and increase children’s active participation in the learning process. In addition, it also supports the development of children’s cognitive abilities, especially in recognizing basic concepts and solving simple problems. In conclusion, the play-based learning method is effective in supporting the cognitive development of early childhood learners at TK Bakti Angkasa Semuli Jaya.